2012
DOI: 10.1371/journal.pone.0032769
|View full text |Cite
|
Sign up to set email alerts
|

Priming with a Recombinant Pantothenate Auxotroph of Mycobacterium bovis BCG and Boosting with MVA Elicits HIV-1 Gag Specific CD8+ T Cells

Abstract: A safe and effective HIV vaccine is required to significantly reduce the number of people becoming infected with HIV each year. In this study wild type Mycobacterium bovis BCG Pasteur and an attenuated pantothenate auxotroph strain (BCGΔpanCD) that is safe in SCID mice, have been compared as vaccine vectors for HIV-1 subtype C Gag. Genetically stable vaccines BCG[pHS400] (BCG-Gag) and BCGΔpanCD[pHS400] (BCGpan-Gag) were generated using the Pasteur strain of BCG, and a panothenate auxotroph of Pasteur respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 60 publications
1
42
1
3
Order By: Relevance
“…The safety of our ⌬panCD BCG vaccine was indicated by the development of fewer granulomas in the spleen and a reduced level of inflammation in the liver of vaccinated mice compared with the corresponding wild-type BCG recombinant results (49). The safety of BCG-vectored vaccines is a relevant issue, as vaccination of HIVinfected children with a clinical BCG (wild type) has been observed to be responsible for mycobacterial disease in 10% of these immunocompromised individuals (31,33).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The safety of our ⌬panCD BCG vaccine was indicated by the development of fewer granulomas in the spleen and a reduced level of inflammation in the liver of vaccinated mice compared with the corresponding wild-type BCG recombinant results (49). The safety of BCG-vectored vaccines is a relevant issue, as vaccination of HIVinfected children with a clinical BCG (wild type) has been observed to be responsible for mycobacterial disease in 10% of these immunocompromised individuals (31,33).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that priming with this rBCG vaccine (rBCGpan-Gag), in a prime-boost combination with an antigen-matched recombinant MVA, elicits HIV-specific CD8 ϩ T cells in mice (49). This study sought to further evaluate the immunogenicity of this rBCG vaccine prime/ Gag VLP boost in nonhuman primates by characterizing the cellular immune response generated in immunized animals in terms of breadth, polyfunctionality, and phenotype of memory T cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations